Avaliação clínica, laboratorial e microbiológica do tratamento com pastas antibióticas de dentes permanentes com rizogênese incompleta necrosados por trauma - Barbosa, Adriana Kelly de Sousa Santiago (2016)
The aim of this study was to evaluate the effects of an antimicrobial paste on the treatment of necrosed to trauma permanent teeth and to verify the presence of microorganisms in the root canal as well as to identify them by performing the polymerase chain reaction (PCR). Thus, two studies were performed: a clinical and microbiological investigation and another one in vitro. Patients who presented open apex necrosed anterior permanent teeth due to trauma and incomplete rhizogenesis were eligible to participate. In the in vitro study, 60 single-rooted specimens were used and their length and root apical diameter were standardized, being contaminated with Enterococcus faecalis for 30 days. In the clinical trial, patients underwent the clinical procedures of the revascularization technique that uses sodium hypochlorite and double antibiotic paste to disinfect the root canal and aggregated trioxide mineral (MTA) as biocompatible material to seal the root canal cervical third. The purpose was to investigate the efficacy of the double antimicrobial paste action through microbiological assessment by bacterial growth analysis and PCR technique in samples collected after endodontic access (C1), after sodium hypochlorite (2.5%) irrigation (C2) and at the end of a 30-day period of use of the double antimicrobial paste in the root canal (C3). The clinical success was assessed by observing the rhizogenesis, dentinary wall thickening, and apex closing through periapical radiographs and localized tomography. Also, the absence of signal and symptoms was evaluated, as well as the absence of periapical lesions. 14 patients were treated, 7 male subjects (50%) and 7 female subjects (50%) whose age ranged from 6-14 years old. Most part of the teeth was affected by lateral luxation (73.3%) and the other (26,3%) cases of dental trauma were avulsion, intrusion, extrusion, and subluxation associated or not with crown fracture without pulp exposition. The percentage of the success reaching 93%. In other words, 14 out of 15 treated teeth presented complete apex closing until the last follow-up examination. Regarding the in vitro study, our purpose was to evaluate the efficacy of the double antimicrobial paste through microbiological evidence in samples collected after the endodontic access (collection 1), after sodium hypochlorite (2.5%) irrigation (collection 2) and at the end of a 30-day period of use of the double antimicrobial paste in the root canal (collection 3). In the 14 teeth from which bacterial samples were collected, it occurred a significant reduction in the colony forming unit (CFU) numbers at the collection 1 (27.1±2.5) to the collection 2 (9.8±1.2), and from this one to the collection 3 (1.3±0.5) (p<0.001). It can be also observed that there was a significant reduction in the number of samples that presented DNA bands for the universal 16 s primer from the collection 1 (n=15, 100.0%) to the collection 3 (n=3, 20.0%) (p<0.001) and E. faecalis DNA from the collection 1 (n=5, 33.3%) to the collections 2 and 3 (n=0, 0.0%) (p=0.004). No sample presented the P. gingivalis bacterial DNA at any collection moment (p=1.000). In the in vitro study, dental specimens were prepared and contaminated with E. faecalis previously to the treatment with different antimicrobial pastes. The analysis was divided in 5 groups: G1 – triple antimicrobial paste (metronidazol, ciprofloxacin, and minocycline), G2 – double antimicrobial paste (metronidazol and ciprofloxacin); G3 – amoxicillin paste; G4 – Calen (calcium hydroxide paste); and G5 – physiological solution (negative control). In the negative control group – G5 no intracanal medication was used. All the groups consisted of 12 dental specimens. In all groups, microbiological collections (C) were carried out using sterile absorbent paper tips before the chemical preparation – C1 and in the respective days for the sample collection and evaluation of the root medication that occurred on the days 7, 14, 21, and 30 of use of the intra-canal medication – C2. The purpose here was to verify the presence of microorganisms in the root canals that were previously contaminated with E. faecalis inoculum. It can be observed that in the group treated with the triple antimicrobial paste, there was no change in the CFU numbers on the 7th day. However, there was a significant reduction on the other days of study (p<0.001). In the group treated with the double antimicrobial paste, there was a significant reduction in the number of CFU on days 7 (p=0.022) and 21(p<0.001), which showed no different from the days 14 and 30. In the amoxicillintreated group, only on the 21st day (p<0.001) it can be observed a significant decrease in the CFU numbers. The treatment with the Calen paste did not alter the CFU numbers on days 7 and 30 (p=0.338). It did, however, significantly alter the CFU numbers on days 14 and 21 (p=0.011). Lastly, there was no significant reduction in the CFU numbers in the negative control group before and after the treatment on days 7, 14, 21, and 30 (p=0.248). Considering the CFU number variation (Δ), there was a significant reduction in the Δvalue of the double antimicrobial paste group in comparison with the negative control on days 14 and 21, as well as the group treated with amoxicillin and triple antimicrobial paste on the 21st day (p<0.001). It can be concluded that the treated teeth showed clinical and radiographic resolution. Further, most of the treated teeth showed radicular length increase, root wall thickening, and apex closing in the follow-up period. Also, we can observe that the antimicrobial pastes, among them the triple and double ones, presented excellent inhibitory effects on E. faecalis. The two pastes were more efficient in reducing the E. faecalis growth than the calcium hydroxide paste. Hence, the double antimicrobial paste can be considered an antimicrobial agent efficient and comparable to the triple antimicrobial and calcium hydroxide pastes.